Madura Batik Ethnomatematics: Mathematical Reasoning in Plane Figures - Shela Hardidesti Mariska; Retno Marsitin; Riski Nur Istiqomah Dinnullah (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
The ethnomathematics approach can simplify mathematical reasoning for students while introducing cultural knowledge. Mathematical concepts in culture are discovered through mathematical reasoning. This research is important to conduct because Madurese batik motifs contain the concept of flat shapes and mathematical reasoning which have the potential to become a source of contextual mathematics learning based on local culture.The purpose of this study is to describe students' mathematical reasoning in Madurese batik ethnomathematics, particularly in plane geometry, through mathematical reasoning indicators. This study adopted a qualitative descriptive research method. The researcher selected 20 participants as subjects and grouped them into high, medium, and low groups based on the results of the reasoning test answers that had the same tendency in writing steps and answers. Therefore, the interview process used two students per group. Data processing was carried out through descriptive analysis and triangulation analysis based on the test results, interviews, and field notes. The results were then reduced, followed by data presentation and conclusion drawing. The results of the study showed that the achievement of mathematical reasoning indicators with all students being able to make assumptions about problems, 16 students being able to prepare mathematical steps, 16 students being able to make conclusions about answers, and 3 students being able to provide arguments/reasons as truth. In addition, at high mathematical reasoning ability, students were able to fulfill all mathematical reasoning indicators. At medium mathematical reasoning ability, students were able to fulfill two mathematical reasoning indicators. At low mathematical reasoning ability, students were not able to fulfill the mathematical reasoning indicators.These results suggest that implementing ethnomathematics can facilitate students' mathematical reasoning. This research has implications for the development of ethnomathematics-based contextual mathematics learning that can enhance mathematical reasoning while preserving Madurese batik culture.